An Analysis of the Implementation of the Policy to Integrate of National Defense Components in Managing Non-Military Threats in the Health Sector - Winarno, Sugeng; Soewondo, Prastuti (UI Scholars Hub, 2016)
This research was based on the Minister of Defense’s Decree No. 16/2012 that stated that all national defense components to integrate into one unit when they encounter military and non-military threats. The Ministry of Health, as the main player, and other governmental and private agencies would also play a role in overcoming complex and multidimensional non-military threats, especially in the health sector. Among those threats are infectious diseases such as HIV/AIDS and Ebola. We aim to discover the implementation process of the law above in the management of those two diseases. This was a qualitative analytical research with in-depth interviews. From this research we discovered that there are several confounding factors in both the main and supporting elements of the implementation, they are the lack of socialization for the policy and fragmented management of the resources and early awareness. We recommend that the ministry increase the socialization and coordination between all stakeholders of all the sectors and from the central to the regional government.